Psychological dynamics of pandemic resilience: a tale of two cultures - Shazia Rehman; Erum Rehman; Akhlaq Awan (Taylor & Francis Group, 2024)
The present work endeavours to explore the experiences of university-level students from Pakistan and Nepal after the COVID-19 outbreak. A comprehensive electronic survey was carried out utilising a meticulous cluster sampling technique encompassing two distinct populations, i.e. Pakistan and Nepal, during the period extending from September 2022 to January 2023. A total of 2496 participants completed the questionnaire (Pakistani population: 55.45% and Nepalese population: 44.55%). We utilised the Mental Health Continuum-Short Form (MHC-SF), Pittsburgh Sleep Quality Index (PSQI), feeling of loneliness (UCLA), interdependent happy scale (IHS), and fear of COVID-19 scale (FCV-19S). Notably, a significant intercultural disparity was observed, particularly concerning the level of COVID-19 fear which was higher among the Nepalese population. However, this particular variable did not demonstrate any significant associations with other variables, except for the social dimension of MHC-SF. There was a negative correlation observed between this variable and IHS within the Pakistani population. Irrespective of the varying degrees of apprehension towards COVID-19 within the two distinct cultural contexts, there exists a significant positive correlation between the assessed psychological assets and individual well-being, as well as the resumption of regular activities after the outbreak.